The Effect Of Additional Types Of Artificial Feed And Different Feed Dosages On The Growth Of Juvenile Snakehead Fish (Channa striata) - Yulfiperius Yulfiperius; Firman Firman; Afan Mahmudin; Risnita Tri Utami (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to determine the effect of giving different types of artificial feed and feed dosages on the growth of snakehead fish (Channa striata) seeds. This research was carried out in January-March for 60 days in Central Bengkulu Regency, Bengkulu Province. The test fish used were snakehead fish seeds measuring 4-6 cm. The method used was a factorial Completely Randomized Design (CRD) with two factors, where the first factor consisted of two treatment levels and the second factor consisted of three treatment levels and was repeated four times (order 2x3x4). The first factor is the provision of artificial feed with 39-41% protein (J1), and 34% protein (J2), while the second factor is the dose with a dose of 3% (D1), a dose of 4% (D2), and a dose of 5% (D3). Each treatment was repeated four times. The research data were analyzed using variance and then continued with the LSD further test. The results showed that the type of artificial feed and different doses significantly affected feed conversion, feed efficiency, and daily growth rate. The best treatment for the daily growth of snakehead fish from the LSD further test was the J1D3 treatment with artificial feed containing 39-40% protein and a dose of 5%.